The Effect Of Social Media Health Protocol Covid 19 On Attitude Changes Based On Persuasion Communication - Donny Tri Wahyudi; Mega Octamelia (International Journal of Health and Pharmaceutical (IJHP), 2022)
Information disseminated in the media has many options for the public to access information. The growing role of social media has different characteristics. The purpose of this study was to analyze the effect of social media on the COVID-19 health protocol on attitude change based on persuasive communication. The results showed that there was an effect of social media on the covid 19 health protocol on attitude change, which was p=0.031<α=0.05. There is a very strong positive relationship between social media and attitude change. Provision of health information is expected through social media by looking at the context of clear and concise messages.